2017
DOI: 10.1093/mnras/stx870
|View full text |Cite
|
Sign up to set email alerts
|

Quasars with P v broad absorption in BOSS data release 9

Abstract: Broad absorption lines (BALs) found in a significant fraction of quasar spectra identify high-velocity outflows that might be present in all quasars and could be a major factor in feedback to galaxy evolution. Understanding the nature of these flows requires further constraints on their physical properties, including their column densities, for which well-studied BALs, such as C iv λλ1548,1551, typically provide only a lower limit because of saturation effects. Low-abundance lines, such as P v λλ1118,1128, ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…Our finding in PG 1411+442 that the Fe ii and Fe ii* lines require an intense radiation field behind a thick layer of fully-ionised gas suggests that the main parameter driving the progression from HiBALs to LoBALs and FeLoB-ALs is larger total column densities, not smaller ionisation parameters and larger distances from the quasars. This is supported by recent work indicating that BAL outflows typically have large ionisation parameters, log U −0.5, and large column densities in ionised gas, log N H (cm −2 ) 22.7, based on measurements of P v BALs in median composite BAL quasar spectra (Hamann et al 2019, see also Hamann & Ferland 1999;Hamann et al 2002;Leighly et al 2011;Borguet et al 2013;Capellupo et al 2017;Moravec et al 2017). The Hamann et al (2019) study shows further that the stronger low-ionisation lines in LoBALs are accompanied by stronger P v absorption compared to HiBALs.…”
Section: Column Densities Distances and Felobalssupporting
confidence: 72%
“…Our finding in PG 1411+442 that the Fe ii and Fe ii* lines require an intense radiation field behind a thick layer of fully-ionised gas suggests that the main parameter driving the progression from HiBALs to LoBALs and FeLoB-ALs is larger total column densities, not smaller ionisation parameters and larger distances from the quasars. This is supported by recent work indicating that BAL outflows typically have large ionisation parameters, log U −0.5, and large column densities in ionised gas, log N H (cm −2 ) 22.7, based on measurements of P v BALs in median composite BAL quasar spectra (Hamann et al 2019, see also Hamann & Ferland 1999;Hamann et al 2002;Leighly et al 2011;Borguet et al 2013;Capellupo et al 2017;Moravec et al 2017). The Hamann et al (2019) study shows further that the stronger low-ionisation lines in LoBALs are accompanied by stronger P v absorption compared to HiBALs.…”
Section: Column Densities Distances and Felobalssupporting
confidence: 72%
“…We also searched for P vλλ1112,1118 absorption in our significant-variability sample. P v is a lower-abundance ion that has an ionization energy similar to that of C iv, and its presence, like that of Si iv, indicates that the corresponding component of C iv absorption is highly saturated (e.g., Capellupo et al 2017). There have been differing reports on the frequency of P v BALs; Capellupo et al (2017) (2014) report that 88% of their C iv SA troughs show detectable P v, about half of the C iv S0 troughs show detectable P v, and only 12% of C iv 00 troughs are accompanied by P v absorption.…”
Section: P Vmentioning
confidence: 99%
“…P v is a lower-abundance ion that has an ionization energy similar to that of C iv, and its presence, like that of Si iv, indicates that the corresponding component of C iv absorption is highly saturated (e.g., Capellupo et al 2017). There have been differing reports on the frequency of P v BALs; Capellupo et al (2017) (2014) report that 88% of their C iv SA troughs show detectable P v, about half of the C iv S0 troughs show detectable P v, and only 12% of C iv 00 troughs are accompanied by P v absorption. The discrepancy in the P v detection percentages between Capellupo et al (2017) andFiliz Ak et al (2014) is likely due to differing identification criteria: Capellupo et al (2013) note that they are extremely conservative in identifying P v and that their algorithm is biased against weaker and narrower features, whereas Filiz Ak et al…”
Section: P Vmentioning
confidence: 99%
“…The detection rate of P v absorption lines in quasar outflows has not been established due primarily to blending problems in the Lyα forest. Capellupo et al (2017) identified a sample of 167 BAL quasars with definite or probable P v absorption based on visual inspection of spectra in the Baryon Oscillation Spectroscopic Survey (BOSS, Dawson et al 2013;Pâris et al 2017) of the Sloan Digital Sky Survey III (SDSS-III, Eisenstein et al 2011). Some of the quasars in that study have clearly-resolved P v doublets troughs that reveal ∼1:1 depth ratios, such that the P v itself is saturated and the total outflow column densities could be much larger than the lower limit mentioned above.…”
Section: Introductionmentioning
confidence: 99%